2022
DOI: 10.3390/nu14235070
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K1 and K2 in the Diet of Patients in the Long Term after Kidney Transplantation

Abstract: Vitamin K, especially its K2 form, is considered to be a protective factor against developing vascular changes and bone lesions that are common complications in kidney transplant (KTx) recipients. There is a growing number of studies showing that KTx patients are at risk of vitamin K deficiency. The aim of this study was to evaluate the intake of vitamin K1 and K2 in the diet of patients in the late period after KTx. During a routine visit at one outpatient transplantation clinic in Central Europe, a diet surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The present meta-analysis found that vitamin K status or supplementation of vitamin K was not related to systolic blood pressure, diastolic blood pressure, triglycerides, hemoglobin, calcium, or 25-hydroxyvitamin D in patients receiving kidney transplantation. A possible reason may be that the disease conditions were complicated in patients after kidney transplantation, and the change of a single factor (vitamin K) does not greatly influence these vascular and bone health indexes; thus, the benefits of vitamin K alone in improving vascular and bone health would not be notable ( 27 , 33 , 34 ). Heterogeneity of systolic blood pressure, triglycerides, hemoglobin, calcium, and 25-hydroxyvitamin D existed among the analyzed studies; meanwhile, sensitivity analysis found that omitting Boxma et al ( 14 ) and Lees et al ( 19 ) affected the results of systolic blood pressure and hemoglobin, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The present meta-analysis found that vitamin K status or supplementation of vitamin K was not related to systolic blood pressure, diastolic blood pressure, triglycerides, hemoglobin, calcium, or 25-hydroxyvitamin D in patients receiving kidney transplantation. A possible reason may be that the disease conditions were complicated in patients after kidney transplantation, and the change of a single factor (vitamin K) does not greatly influence these vascular and bone health indexes; thus, the benefits of vitamin K alone in improving vascular and bone health would not be notable ( 27 , 33 , 34 ). Heterogeneity of systolic blood pressure, triglycerides, hemoglobin, calcium, and 25-hydroxyvitamin D existed among the analyzed studies; meanwhile, sensitivity analysis found that omitting Boxma et al ( 14 ) and Lees et al ( 19 ) affected the results of systolic blood pressure and hemoglobin, respectively.…”
Section: Discussionmentioning
confidence: 99%